Risks of Simultaneous Coinfection of Dengue and COVID-19 in Bangladesh: Challenges and Recommendations - Md. Sahidur Rahman; Tazrina Rahman (Dr. Sulaiman Al Habib Medical Journal)
The current global Coronavirus Disease 2019 (COVID-19) pandemic is compounding on populations susceptible to tropical illnesses such as dengue in different developing countries such as Bangladesh. The growing concern is that Bangladesh is a dengue-endemic zone and the peak transmission occurs in the monsoon season (June to October). In the most recent monsoon, a total of 354 dengue cases have been confirmed until July 27, 2020, data-driven from only 41 hospitals alone. A 53-year- old male patient was found to be coinfected with COVID-19 and dengue fever in Bangladesh. Concerns arise as hospitals are increasingly denying admission to patients. Moreover, reports of false-positive results in dengue screening tests recorded in different countries further exacerbate the issue. These conditions could postpone the early diagnosis of COVID-19 cases and aggravate the situation. In addition, the overwhelming wave of dengue cases would be a challenge for the vulnerable healthcare system of the country, which is already under strain because of the COVID-19 pandemic. Failure to establish and implement proper policies might lead to dengue outbreak with the burdens of the concurrent COVID pandemic, resulting in the collapse of the health and social systems, as well as the economic growth of the country.